Green Urban Infrastructure and the Potential for Offering Ecosystem Services for Climate Adaptation: Land Use Analysis of the Pinheiros District (São Paulo) - Monteiro, Gracielli Folli; Gallardo, Amarilis Lucia Casteli Figueiredo; Cortese, Tatiana Tucunduva Philippi; Nascimento, Ana Paula Branco (National Journal of City Management, 2022)
Ecosystem services (ES) represent various benefits to society, especially those of climate regulation. An increasing number of recommendations are being made so that urban planning internalizes the concept of ES to objectively measure these benefits or for decision making. This paper intends to analyze the role of green infrastructure in urban land use to address the potential for providing climate regulation ES in urban green areas as measures of Ecosystem Based Adaptation (EbA). To this end, it was selected as a case study the land use analysis of the Pinheiros District in São Paulo. This region has a high degree of waterproofing, but has significant green areas and potential space to incorporate the expansion of green infrastructure, i.e., to promote EbA strategies, and consequently the offering of ES. For this purpose, geospatial analysis was used with the technical subsidies of a methodology proposed to measure the capacity of different extensions of vegetation coverage to promote ES regulation. The application showed that one of the district’s four sub-districts revealed an existing and greater potential to mitigate climate change effects than the other three sub-districts. This discussion is considered timely given the recently released 2021 Climate Action Plan for the Municipality of São Paulo. The results of the work can be considered by public managers and decision makers on the role of urban green areas and their potential for climate adaptation.